2013
DOI: 10.1186/bcr3405
|View full text |Cite
|
Sign up to set email alerts
|

Risk of breast cancer in Lynch syndrome: a systematic review

Abstract: IntroductionLynch syndrome is an autosomal dominantly inherited disorder of cancer susceptibility caused by germline mutations in the DNA mismatch repair (MMR) genes. Mutation carriers have a substantial burden of increased risks of cancers of the colon, rectum, endometrium and several other organs which generally occur at younger ages than for the general population. The issue of whether breast cancer risk is increased for MMR gene mutation carriers has been debated with evidence for and against this associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 76 publications
2
77
1
1
Order By: Relevance
“…In addition, there have been suggestions of an increased risk for breast cancer in the Lynch syndrome population 76,77 ; however, there is insufficient evidence to support increased screening above average-risk breast cancer screening recommendations. 42,51 A study of 188 men with Lynch syndrome also showed a 5-fold increase in risk of prostate cancer.…”
Section: Surveillance For Patients With Lynch Syndromementioning
confidence: 99%
“…In addition, there have been suggestions of an increased risk for breast cancer in the Lynch syndrome population 76,77 ; however, there is insufficient evidence to support increased screening above average-risk breast cancer screening recommendations. 42,51 A study of 188 men with Lynch syndrome also showed a 5-fold increase in risk of prostate cancer.…”
Section: Surveillance For Patients With Lynch Syndromementioning
confidence: 99%
“…Although several studies have suggested there is no increased risk for breast cancer with LS, there has been no consensus to date on the correlation between breast cancer and LS [11,12,13,19,20]. This study revealed that 22.4% of the LS patients meeting NCCN criteria for HBOC had a personal history of breast cancer and a family history of early-onset breast cancer.…”
Section: Discussionmentioning
confidence: 66%
“…With the experience of gene panels, which included HBOC susceptibility genes among others, some families harboring a mutation in an MMR gene did not meet Amsterdam II or Bethesda criteria for Lynch syndrome testing [37]. To date, it is unclear whether the results in our three families with single-affected earlyonset BC should be regarded as incidental or not since an increased risk of BC in Lynch syndrome is still controversial [38][39][40]. Nevertheless, massively-parallel sequencing targeting multiple candidate genes is changing the paradigm as it gives the opportunity to assess the role of genes that would never have been evaluated in a nonpanel approach.…”
Section: Discussionmentioning
confidence: 99%